Belonging to neo-tribes or just glocal youth talk: Jewish Israeli adolescent girls representing themselves on Facebook. (1st June 2014) - Levin, David; Barak-Brandes, Sigal
This article examines the role of Facebook language tools in shaping and preserving community limits among Jewish Israeli adolescent girls, who constitute a young, dynamic, western and age-specific community. We describe how actions such as confirming friend requests, updating statuses and assigning 'likes' serve as means of phatic communication and as deictic elements that sketch out the community's limits. Based on interviews with eight focus groups comprising a total of 35 Israeli adolescent girls, we challenge the prevalent view that social networks and the Internet in general facilitate fast and superficial transitions between sites and identities. Quite the contrary, we argue that these ostensibly random transitions in fact set clear limits by means of apparently banal authorizations of belonging to a community that occur on a daily basis. These community limits set by this youth communication are more rigid and conservative than those apparent in these girls' everyday lives offline.